Youth and the Politics of the Present Coping with Complexity and Ambivalence - Colombo, Enzo; Rebughini, Paola (Routledge Advances in Sociology, 2019)
Youth and the Politics of the Present presents a range of topical sociological investigations into various aspects of the everyday practices of young adults in different European contexts. Indeed, this volume provides an original and provocative investigation of various current central issues surrounding the effects of globalization and the directions in which Western societies are steering their future. Containing a wide range of empirical and comparative examples from across Europe, this title highlights how young adults are trying to implement new forms of understanding, interpretation and action to cope with unprecedented situations; developing new forms of relationships, identifications and belonging while they experience new and unprecedented forms of inclusion and exclusion. Grounding this exploration is the suggestion that careful observations of the everyday practices of young adults can be an excellent vantage point to grasp how and in what direction the future of contemporary Western societies is heading. Offering an original and provocative investigation, Youth and the Politics of the Present will appeal to students and researchers interested in fields such as Youth Studies, Globalization Studies, Migration Studies, Gender Studies and Social Policy.